TRANSLATION STRATEGIES: TRANSLATING LOCAL SHORT STORIES FROM INDONESIAN INTO ENGLISH (RETAIN, 2020)
In translating a language, a translator needs to implement translation strategies in order to find or create exact language equivalences from SL (Source Language) into TL (Target Language) especially for EFL learner in university that taking translation as the learning subject. Some previous studies have mentioned translation strategies that have been implemented in translation such as book titles, brand names and English children literature’s names of characters. Some previous studies only focus on finding translation strategies in translating some terms. However in this research, the researcher focused on analyzing translation strategies in translating local short stories. The data were collected through document analysis. The aims of this research were to find translation strategies EFL students used in translating local short stories and the way EFL students translated local short stories by using some kinds of translation strategies. The results of this research found that translation strategies that EFL students have implemented are literal translation, word to word translation, free translation and semantic translation. However, the researcher also found that EFL students have misinterpretation toward semantic translation and tends to categorize semantic translation to other translation strategies. Keywords: translation, local short stories, translation strategies, source language (SL), target language (TL)